2017
DOI: 10.1155/2017/2184040
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Healing of a Cutaneous Wound in an Inducible Nitric Oxide Synthase-Knockout Mouse

Abstract: Background. We investigated the effects of loss of inducible nitric oxide synthase (iNOS) on the healing process of cutaneous excisional injury by using iNOS-null (KO) mice. Population of granulation tissue-related cell types, that is, myofibroblasts and macrophages, growth factor expression, and reepithelialization were evaluated. Methods. KO and wild type (WT) mice of C57BL/6 background were used. Under general anesthesia two round full-thickness excision wounds of 5.0 mm in diameter were produced in dorsal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 36 publications
2
19
0
Order By: Relevance
“…In our study, we showed that, 14 days after hyperglycaemic onset, there is iNOS production at a level that continues to increase with time. Some level of iNOS is necessary for wound healing as knockout mice for iNOS showed impaired wound healing; however, as shown in this study, overproduction of iNOS is also correlated with prolonged inflammation within the dermis and delays wound healing. As we mentioned earlier, HbO 2 is a scavenger for NO and is one of the main pathways through which the body eliminates NO .…”
Section: Discussionsupporting
confidence: 48%
“…In our study, we showed that, 14 days after hyperglycaemic onset, there is iNOS production at a level that continues to increase with time. Some level of iNOS is necessary for wound healing as knockout mice for iNOS showed impaired wound healing; however, as shown in this study, overproduction of iNOS is also correlated with prolonged inflammation within the dermis and delays wound healing. As we mentioned earlier, HbO 2 is a scavenger for NO and is one of the main pathways through which the body eliminates NO .…”
Section: Discussionsupporting
confidence: 48%
“…Though eNOS and iNOS are both necessary and active in wound healing mechanisms, the moderate levels of NO generated by eNOS regulate inflammation whereas iNOS provides levels of NO that are large enough to eradicate acute infection‐causing pathogens. Previous reports have described wound healing in iNOS‐knockout mice and have found that cutaneous wound healing is severely impaired in the total absence of iNOS . Other studies have conversely found that inhibition of nitric oxide synthase improves ischemia and reperfusion injuries .…”
Section: Endogenous Nitric Oxide For Chronic Wound Therapymentioning
confidence: 97%
“…Previous studies have showed that either deficiency in or inhibition of iNOS delays cutaneous wound healing. [ 7,8 ] Conversely, topical applications of nitric oxide accelerate cutaneous wound healing. [ 9 ] However, deficiency in either endothelial or neural NOS accelerates epidermal permeability barrier recovery following acute barrier disruption in mice, [ 2 ] while one study showed that knockout of iNOS did not alter epidermal permeability barrier homeostasis in mice.…”
Section: Introductionmentioning
confidence: 99%